Polymorphisms of aquaporin 7 (AQP7) gene in Madura bulls (Bos indicus) - HARTATI; PUTRA, WIDYA PINTAKA BAYU (The Indian Journal of Animal Sciences, 2022)
In this study, a PCR-RFLP method was employed to investigate the evidence of two mutation sites in exon 2 (c.N8S) and exon 3 (c.E36Q) regions of AQP7/TaaI gene in Madura bulls. Both mutation sites were polymorphic with presence of three genotypes. However, a mutation of c.N8S had the moderate PIC value (>0.30). Hence, it can be suggested that the mutation of c.N8S can be used for the genetic marker of sperm quality traits in Madura bulls. However, the association study with 15 selected Madura bulls revealed that there are no significant association between c.N8S and sperm quality traits. However, the mutation of c.N8S in animal studies was not associated with sperm quality traits of sperm volume, progressive motility sperm concentration and daily sperm viability. In future, a further research with large number of animal samples and records data are important to obtain the genetic markers for productivity traits accurately.